2012
DOI: 10.1007/s00586-012-2616-1
|View full text |Cite
|
Sign up to set email alerts
|

Access related complications in anterior lumbar surgery performed by spinal surgeons

Abstract: We report a very thorough and critical review of our anterior lumbar access surgeries performed mostly for DDD and spondylolisthesis at L4/5 and L5/S1 levels. Vascular problems of any type (24/304, 7.8 %) were the most common complication during this approach. The incidence of major venous injury requiring repair was 14/304 (4.6 %) and arterial injury 5/304 (1.6 %). The requirement for a vascular surgeon with the vascular injury was 9/304 (3 %; 5 arterial injuries; 4 venous injuries). This also suggests that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
79
0
4

Year Published

2013
2013
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 135 publications
(88 citation statements)
references
References 19 publications
5
79
0
4
Order By: Relevance
“…Apart from the vascular injuries, the only complication with a potential harm to the patient was a pulmonary embolism in a patient who had a venous injury, which was postoperatively managed with anticoagulation. In a recently published study, the overall complication rate in a younger patient population was 20 % [7]. While it has been reported that anterior access to the lumbar spine is associated with a risk of vascular injury, the reported rates of injury are reasonably low with or without a vascular access surgeon [6,7].…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Apart from the vascular injuries, the only complication with a potential harm to the patient was a pulmonary embolism in a patient who had a venous injury, which was postoperatively managed with anticoagulation. In a recently published study, the overall complication rate in a younger patient population was 20 % [7]. While it has been reported that anterior access to the lumbar spine is associated with a risk of vascular injury, the reported rates of injury are reasonably low with or without a vascular access surgeon [6,7].…”
Section: Discussionmentioning
confidence: 98%
“…Particular attention was given to document all accessrelated intraoperative complications such as vascular injury, injury to ureter or kidney, bowel injury, and incidental opening of peritoneum, neurological injury, dural tear as well as anaesthetic complications such as problems with airway management or intraoperative circulatory problems. Vascular injury was defined as major if it required repair or reconstruction as previously defined [6,7]. Minor vascular injuries such as bleeding while mobilizing the vessels or ligating the iliolumbar vein that were treated with pressure or a haemostatic agent were not recorded in this study.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Quraishi and his team studied 304 patients in England nding that there are 4.6% venous injuries that needed to be repaired and 1.6% arterial injuries. 22 Brau and his team found in 1,315 patients 0.5% arterial injuries and 1.4% venous injuries. There are a lot more reports about this risk.…”
Section: Buranakarl T and Jaisanuk Kmentioning
confidence: 98%
“…Despite it being an anterior surgery through the retroperitoneum, adjacent organs and blood vessels could be endangered. 22,23 Therefore, professional experience is needed for operating the intervertebral disc area close to arteries and veins. Quraishi and his team studied 304 patients in England nding that there are 4.6% venous injuries that needed to be repaired and 1.6% arterial injuries.…”
Section: Buranakarl T and Jaisanuk Kmentioning
confidence: 99%